Personality as extralinguistic factor that influences second language learning among foreign students - Kamaruddin, Rohaidah; Kamaruddin, Azni Yati; Seruji, Zuraini (Asian Economic and Social Society, 2019)
The researchers conducted this study to determine the relationship between second language extralinguistic factors with Malay achievement among foreign students at five universities in Malaysia. The researchers were interested to address colour personality as extralinguistic factor that influences second language learning among foreign students at universities in Malaysia. The findings showed that foreign students? personality was influenced by green, red and yellow which indicated that they are willing to do anything to succeed and acquire the second language. The sample of this study comprises 150 students from 27 countries. They took Malay as a foreign language at Putra University of Malaysia (UPM), National University of Malaysia (UKM), University of Malaya (UM), University of Technology Malaysia (UTM) and University of Science Malaysia (USM).